Strategi Manajemen Eksternal Berbasis Keberlanjutan dalam Program Bakti BCA pada Bank Central Asia - Ramadhan, Yanuar; Arnanda, Rifky Arya; Budiani, Selsa Mahfuza; Mayshandi, Justin; Putri, Chesterita; Tambunan, Nessa Agustina (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the role of BAKTI BCA as a strategic initiative in strengthening external stakeholder engagement and corporate sustainability at PT Bank Central Asia (BCA). The research focuses on how structured corporate social responsibility (CSR) practices can be integrated into strategic management to support long-term legitimacy and organizational resilience. Adopts a qualitative descriptive approach using a literature review method. The primary sources of data include the 2024 BCA Sustainability Report, peer-reviewed academic journal articles, and information from the official website of PT Bank Central Asia. Data were collected through document analysis and examined using interpretive and thematic techniques, guided by theoretical frameworks on strategic management, stakeholder engagement, corporate social responsibility (CSR), and environmental, social, and governance (ESG) principles. Finds that BAKTI BCA functions as a strategic platform that links corporate vision with external sustainability goals. With programs in education, economy, health, culture, and environment, BAKTI BCA demonstrates how corporations can move beyond symbolic CSR and create measurable impact. It contributes significantly to stakeholder trust, strengthens BCA’s ESG standing, and aligns corporate operations with national sustainable development goals. The integration of CSR as a longterm strategy enhances institutional reputation and supports social and environmental value creation.